Reproducibility of T2 relaxation time mapping in a phantom and human knee articular cartilage - Henri P. P. Leskinen; Nea Pulkkinen; Antti Aarnio; Amir Esrafilian; Teija Sainio; Eveliina Lammentausta; Ville Kantola; Victor Casula; Simo Ojanen; Jari Rautiainen; Petri Kaurola; Mimmi K. Liukkonen; et al. (Magnetic Resonance Materials in Physics, Biology and Medicine, 2026)
Abstract Objective To quantify the reproducibility of knee articular cartilage T2 across a wide range of MR systems. Materials and methods The reproducibility of T2 relaxation time mapping was assessed by measuring the knee of a volunteer (n 1.5 T = 22, n 3T = 13) and a System Standard 130 phantom (n 1.5 T = 19, n 3T = 12) in 38 different clinical MRI scanners at 16 imaging sites. Root-mean-square coefficient of variation (CV RMS ) was used to quantify the reproducibility of T2 at the selected knee cartilage regions of interest (ROI) and the phantom T2 array vials. Results Low-to-moderate inter-scanner variation for the knee ROIs, CV = 2.2% to 22.8%, CV RMS,1.5 T = 9.3%, CV RMS,3 T = 11.0%, was observed. The phantom measurements showed low inter-scanner variation (CV RMS, 1.5 T = 4.7%, CV RMS, 3 T = 2.4%) on the typical cartilage T2 range. Discussion Reproducibility of quantitative T2 can vary between healthcare facilities and scanners but also between the cartilage compartments. The variation is sufficiently small to consider T2 mapping reproducible. Phantom measurements support this result.